Prelimbic Ensembles Mediate Cocaine Seeking After Behavioral Acquisition and Once Rats Are Well-Trained - Sortman, Bo W.; Gobin, Christina; Rakela, Samantha; Cerci, Berk; Warren, Brandon L. (Frontiers in Behavioral Neuroscience, 2022)
Substance use disorder (SUD) is a chronic relapsing condition characterized by continued use of drugs despite negative consequences. SUD is thought to involve disordered learning and memory wherein drug-paired cues gain increased salience, and ultimately drive craving and relapse. These types of associations are thought to be encoded within sparsely distributed sets of neurons, called neuronal ensembles, that drive encoded behaviors through synchronous activity of the participant neurons. We have previously found that Fos-expressing neuronal ensembles within the prefrontal cortex are required for well-trained cocaine-seeking. However, less is known about how quickly cortical neuronal ensembles form during initiation of cocaine-seeking behavior. Here, we seek to further elucidate the role of Fos-expressing neuronal ensembles within the prelimbic cortex (PL) after initial acquisition of cocaine self-administration (SA), or, after ten days of additional SA training (well-trained). We trained Fos-LacZ transgenic rats to lever press for cocaine under an FR1 schedule of reinforcement. Once rats met acquisition criteria for cocaine self-administration, we ablated Fos-expressing neuronal ensembles in the PL using the Daun02 inactivation method, either 1 or 10 days after rats met acquisition criteria. Targeted ablation of Fos-expressing neuronal ensembles in the PL attenuated active lever pressing both 1 day and 10 days after rats acquired cocaine self-administration. Together, this suggests that Fos-expressing neuronal ensembles rapidly form in the PL and continue to mediate maintained cocaine-seeking behavior.